Educational Game for Writing and Introduction of Javanese Script Based on Augmented Reality - Desy Fitriana; Sri Wulandari (Jurnal Indonesia Sosial Teknologi, 2025)
The use of augmented reality (AR) in education has become a trend and an innovative solution in the digital era. The application of AR in educational software development is an interesting approach to increasing interest in learning. This research aims to develop an educational game that introduces and teaches Javanese script to users through an interactive and fun experience with AR technology. The methods used include needs analysis, design, development, and evaluation. The results of this research are in the form of an application that presents Javanese script interestingly and interactively through AR. The evaluation was done with black box testing, which showed that the app worked as expected.